Evaluation of placental oxygenation in fetal growth restriction using blood oxygen level-dependent magnetic resonance imaging. (August 2022) - Magawa, Shoichi; Nii, Masafumi; Enomoto, Naosuke; Takakura, Sho; Maki, Shintaro; Tanaka, Hiroaki; Ishida, Masaki; Kondo, Eiji; Sakuma, Hajime; Ikeda, Tomoaki
Abstract: Introduction: Abnormalities in placental function can lead to fetal growth restriction (FGR), but there is no consensus on their evaluation. Using blood oxygen level-dependent magnetic resonance imaging (BOLD MRI), we compared placental oxygenation between FGR cases and previously reported normal pregnancies. Methods: Eight singleton pregnant women (>32 weeks of gestation) diagnosed with fetal growth failure during pregnancy were recruited. BOLD MRI was consecutively performed under normoxia (21% O2 ), hyperoxia (100% O2 ), and normoxia for 4 min each. Each placental time-activity curve was evaluated to calculate the peak score (peakΔR2*) and the time from the start of maternal oxygen administration to the time of peakΔR2* (time to peakΔR2*). In six of the eight FGR cases, placental FGR-related pathological findings were evaluated after delivery. Results: The parameter peakΔR2* was significantly decreased in the FGR group (8 ± 3 vs 6 ± 1, p < 0.001), but there was no significant difference in time to peakΔR2* (458 ± 74 s vs 468 ± 57 s, p = 0.750). The findings in the six FGR cases assessed for placental pathologies included chorangiosis in two cases, avascular chorions in two cases, placental infarction in two cases, and syncytial knot formation in one case. Discussion: The peakΔR2* values were lower in the FGR group than in the normal pregnancy group. This suggests that oxygenation of the placenta is decreased in the FGR group compared to the normal group, and this may be related to FGR. Placental pathology also revealed findings possibly related to FGR, suggesting that low peakΔR2* values in the FGR group may reflect placental dysfunction. Highlights: Pregnant women without or with fetal growth restriction (FGR) were enrolled. Placental oxygenation was assessed with blood oxygen level-dependent (BOLD) MRI. PeakΔR2* of BOLD MRI were decreased in the FGR group. Low peakΔR2* values may reflect placental dysfunction.